2015
DOI: 10.1002/eco.1604
|View full text |Cite
|
Sign up to set email alerts
|

Defoliation effects of Diorhabda carinulata on tamarisk evapotranspiration and groundwater levels

Abstract: Diorhabda carinulata (northern tamarisk beetle) has been released in the western United States as a biological control agent for the invasive plant Tamarix spp. (tamarisk). A few studies have been conducted analysing the effects of beetle defoliation on tamarisk water consumption, but predefoliation and post‐defoliation comparison based on field data is scarce. The question of whether beetles substantially alter tamarisk water consumption is still open for discussion. In this study, an eddy covariance station … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 52 publications
(107 reference statements)
1
17
0
Order By: Relevance
“…For validation purposes, METRIC ET was compared with ground‐based ET estimates obtained by an eddy covariance flux station installed in tamarisk on the Lower Virgin River (Figure ) (Sueki et al, ). A polygon encompassing the approximate eddy covariance flux station footprint was used to spatially average METRIC ET estimates within the footprint at daily time steps (Figure ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For validation purposes, METRIC ET was compared with ground‐based ET estimates obtained by an eddy covariance flux station installed in tamarisk on the Lower Virgin River (Figure ) (Sueki et al, ). A polygon encompassing the approximate eddy covariance flux station footprint was used to spatially average METRIC ET estimates within the footprint at daily time steps (Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…Yearly pre-beetle and post-beetle Lower Virgin ET versus ET r Average yearly ET results for the Lower Virgin and Lower Muddy River are presented in Comparison with eddy covariance flux station ET estimates For validation purposes, METRIC ET was compared with ground-based ET estimates obtained by an eddy covariance flux station installed in tamarisk on the Lower Virgin River (Figure 1) (Sueki et al, 2015). A polygon encompassing the approximate eddy covariance flux station footprint was used to spatially average METRIC ET estimates within the footprint at daily time steps (Figure 1).…”
Section: Pre-beetle and Post-beetle Lower Virgin Monthly Et Versus Et Rmentioning
confidence: 99%
“…Our ET estimates for the five other sites were in rough agreement with previously published rates (Figure , Table ). Previous studies corroborate the use of NDVI for tamarisk stand vigour and water use (Bedford, Sankey, Sankey, Durning, & Ralston, ; Dennison et al, ; Everitt, Yang, Fletcher, Deloach, & Davis, ; Hultine et al, ; Meng et al, ; Nagler et al, ; Nagler et al, ; Sueki et al, ).…”
Section: Discussionmentioning
confidence: 97%
“…Previous, shorter term studies on several western U.S. rivers have all shown that beetle defoliation reduces plant transpiration temporarily (~2-8 weeks), then tamarisk regrows leaves and ET rates recover (Dennison et al, 2009;Hultine, Nagler, et al, 2010;Nagler et al, 2012;Snyder et al, 2012;Sueki et al, 2015). Our current study is unique in that 12 years of measurements were made, during a period when weather encompassed both extreme drought years and two very wet years (Figure 1 Our first hypothesis that beetles would produce a reduction in ET loss and CO 2 uptake, if beetle density remained high, was not supported.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation